Moisture-powered memristor with interfacial oxygen migration for power-free reading of multiple memory states. (May 2020) - Tao, Ye; Wang, Zhongqiang; Xu, Haiyang; Ding, Wentao; Zhao, Xiaoning; Lin, Ya; Liu, Yichun
Abstract: Self-powered memristors have the potential capability to promote highly efficient memory and neuromorphic computing, allowing the exploration of power-free electronics for future. The present study developed a novel moisture-powered memristor, having a multi-layer structure of W/WOx /oxygen-plasma-treated amorphous-carbon (OAC)/Pt. The reversible oxygen migration across the WOx /OAC interface formed between the memristor layer and the nanogenerator layer occurs in this integrated device, which allows simultaneous modulation of resistance state and open circuit voltage (Voc ). This device not only presented the reversible characteristics of resistive switching and moisture-powered reading through human breath, but also further demonstrated the capability of the selective reading of multiple memory states for the first time. Cross-sectional transmission electron microscopy observations provided solid evidence of the important role of interfacial oxygen migration, accounting for the mechanism of Voc modulation and resistive switching. This work provides a feasible strategy to build up the self-powered memristor for constructing highly efficient memristive neural networks. Graphical abstract: Image 1 Highlights: The moisture-powered memristor with interfacial oxygen migration was developed. Power-free multilevel reading capacity for memory was demonstrated. Oxygen migration and oxygen gradient modulation were both verified through TEM observations.